Safeguarding of the social right to pharmaceutical assistance in the state of São Paulo, Brazil - Marques, Silvia Badim; Dallari, Sueli Gandolfi (Revista de saúde pública, 2007)
To evaluate how the Judicial Power safeguards the social right to pharmaceutical assistance as well as the relationships between the legal and political systems to safeguard this right. There were assessed decisions in lawsuits of drug supply in the state of São Paulo, Southern Brazil, between 1997 and 2004. Discourse of the Collective Subject of procedural actors was the methodological approach used. In 96.4% of the cases analyzed, judges' discourse sentenced the State. In these cases, the State was obliged to provide drugs exactly as requested by the plaintiff, even when drugs were not registered in the National Health Surveillance Agency (9.6% of cases). Also, 100% of the lawsuits were proposed by individual plaintiffs; in 77.4% of the cases the plaintiff requested an specific drug of a specific pharmaceutical company; and in 93,5%, the drugs were provided to the plaintiff through an urgent preliminary order. The Judicial Power is not taking into account in its decisions political elements of drug policies, established to enforce the social right to pharmaceutical assistance. The Judicial Power is hindering the collective decision making process by the political system, prioritizing plaintiffs' individual needs over community interests.